High-Level Accumulation of Exogenous Small RNAs Not Affecting Endogenous Small RNA Biogenesis and Function in Plants - Wan-xia SHEN; Neil A Smith; Chang-yong ZHOU; Ming-bo WANG (Journal of Integrative Agriculture, 2014)
RNA silencing is a fundamental plant defence and gene control mechanism in plants that are directed by 20-24 nucleotide (nt) small interfering RNA (siRNA) and microRNA (miRNA). Infection of plants with viral pathogens or transformation of plants with RNA interference (RNAi) constructs is usually associated with high levels of exogenous siRNAs, but it is unclear if these siRNAs interfere with endogenous small RNA pathways and hence affect plant development. Here we provide evidence that viral satellite RNA (satRNA) infection does not affect siRNA and miRNA biogenesis or plant growth despite the extremely high level of satRNA-derived siRNAs. We generated transgenic Nicotiana benthamiana plants that no longer develop the specific yellowing symptoms generally associated with infection by Cucumber mosaic virus (CMV) Y-satellite RNA (Y-Sat). We then used these plants to show that CMV Y-Sat infection did not cause any visible phenotypic changes in comparison to uninfected plants, despite the presence of high-level Y-Sat siRNAs. Furthermore, we showed that the accumulation of hairpin RNA (hpRNA)-derived siRNAs or miRNAs, and the level of siRNA-directed transgene silencing, are not significantly affected by CMV Y-Sat infection. Taken together, our results suggest that the high levels of exogenous siRNAs associated with viral infection or RNAi-inducing transgenes do not saturate the endogenous RNA silencing machineries and have no significant impact on normal plant development.